2017
DOI: 10.1136/bcr-2017-220985
|View full text |Cite
|
Sign up to set email alerts
|

Leg length discrepancy: the importance of a complete history and examination

Abstract: A 26-year-old woman with a 1-year history of right knee pain had failed to respond to analgesia and activity modification in the community. Her general practitioner referred her to the orthopaedic department for specialist review. A thorough history revealed that she had multiple orthopaedic interventions as a child. The patient had significant postoperative infection of the left knee following knee surgery at 7 years of age. Examination demonstrated the presence of a limp, scoliosis and suspected leg length d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Several studies found that LLD is correlated with pelvic tilt in the coronal plane, also called pelvic obliquity 1,2,13,14,[16][17][18] . Some have studied the immediate effects of artificially induced LLDs, using different measuring techniques and showed that LLD affected the pelvic disposition creating pelvic obliquity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that LLD is correlated with pelvic tilt in the coronal plane, also called pelvic obliquity 1,2,13,14,[16][17][18] . Some have studied the immediate effects of artificially induced LLDs, using different measuring techniques and showed that LLD affected the pelvic disposition creating pelvic obliquity.…”
Section: Resultsmentioning
confidence: 99%
“…An LLI, by altering the support of the acetabulum on the femoral head, alters the balance of the pelvis. Several scholars have reported that LLIs are related to pelvic tilt in the coronal plane, which is also called pelvic obliquity [11,42,57,66,71,[95][96][97]. In a sample of 524 patients with degenerative scoliosis and an average age of 60.7 years, Radcliff et al [80] reported that the prevalence of pelvic obliquity in patients with a single degenerative scoliotic curve was 91%.…”
Section: Relationship Between Lli and Pelvic Inclination In Scoliosis...mentioning
confidence: 99%
“…The therapist selects sequence a group manual tests for classification lower limbs discrepancy. The techniques will also be classified according to the type of manoeuvres described in the literature and will be explained in detail [9]. The present paper defines a simple assessment plan for therapists, which is design for LLD in the context of SD assessment.…”
Section: Introductionmentioning
confidence: 99%